The Role of Workload, Job Stress, and Compensation in Enhancing Outsourced Employee Perfomance: Evidence from PT PLN (Persero) Unit Layanan Pelanggan Majalengka - Akhmad Saeful Mulki; Ifan Sihabudin; Sunimah; Anna Suzana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the influence of workload, work stress, and compensation on the job performance of field employees in an energy distribution company. This research uses a quantitative approach with a total sampling method, in which the entire population of 102 field employees is used as respondents. Data were collected using a Likert scale questionnaire and analyzed with the help of the SPSS program. The analysis was carried out through validity and reliability tests, classical assumption tests, and multiple linear regression to examine the influence of each variable on job performance. The results of the study show that: 1) Workload has a positive and significant effect on employee job performance; 2) Work stress has a positive and significant effect on job performance; and 3) Compensation has a positive and significant effect on job performance. Simultaneously, workload, work stress, and compensation significantly influence the job performance of field employees.